AB0498 Optimisation of methotrexate dose induced successful reduction of glucocorticoids without impaired disease control in patients with rheumatoid arthritis. (12th June 2018) - Hirata, S.; Kondo, T.; Yukawa, K.; Tokunaga, T.; Kuranobu, T.; Oi, K.; Yoshida, Y.; Funaki, M.; Oda, K.; Nojima, T.; Sugiyama, E.
Abstract : Background: Use of short-term glucocorticoids (GCs) along with methotrexate (MTX) have been recommended for newly onset patients with rheumatoid arthritis (RA) in EULAR recommendation 2016 However, it is not always easy to reduce or withdraw GCs due to patients' fear of relapsed pain or fatigue. As well, some patients are negative to increase MTX dose for fear of adverse events. Objectives: To clarify whether GCs could be reduced without impaired disease control by optimising MTX dose in RA patients with stable medication in real-world clinical practice setting. Methods: 70 patients with RA who regularly visit our outpatient clinic for ≥1 year were enrolled. Clinical characters, disease activity, and medications at present and 1 year before were retrospectively collected. Therapeutic strategy was to increase MTX with reducing prednisolone (PSL) based on patient's consent. Initiating bDMARDs was allowed in case of uncontrollable disease. Wilcoxon test and chi-square test were used for statistics. Results: Clinical characters (median [IQR]) were; age 62 51, 68 yrs; female 69%; disease duration 6.8 [3.4, 13.7] yrs. Rate of MTX was elevated from 57% to 62%, and dose (mean ±SD) was increased from 9.8±3.2 to 11.6±3.7 mg/w (p<0.0001) for uses only, whereas PSL was suppressed from 56% to 26%, and decreased from 2.0±3.1 to 0.8±1.8 mg/d (p=0.0004) for all patients. bDMARDs were used for 16 patients, and newly initiated for 2 patients. Although not significant, median CDAI, SDAI, and DAS28 were suppressed from 5.7 to 3.8, 6.2 to 3.9, and 2.92 to 2.77, and remission rate were increased from 24% to 39%, 27% to 41%, and 36% to 41%, respectively. Conclusions: GCs could be reduced or withdrawn without deterioration with appropriately increased MTX. Moreover, disease control rather showed improved tendency. Disclosure of Interest: S. Hirata Grant/research support from: Eli Lilly, UCB, Consultant for: Bristol-Myers Squibb, UCB, Paid instructor for: AbbVie, Eisai, Tanabe-Mitsubishi, Speakers bureau: AbbVie, Astellas, Ayumi, Bristol-Myers Squibb, Chugai, Eisai, Eli Lilly, Jansen, Kissei, Pfizer, Sanofi, Takeda, Tanabe-Mitsubishi, UCB, T. Kondo: None declared, K. Yukawa: None declared, T. Tokunaga: None declared, T. Kuranobu: None declared, K. Oi: None declared, Y. Yoshida Speakers bureau: Bristol-Myers Squibb, Chugai, Sanofi, M. Funaki Speakers bureau: Chugai, K. Oda Speakers bureau: Asahi-Kasei, Kissei, Ono, Pfizer, Astellas, Jansen, Tanabe-Mitsubishi, T. Nojima Speakers bureau: Astellas, Ayumi, Bristol-Myers Squibb, Chugai, Sanofi, Tanabe-Mitsubishi, E. Sugiyama Grant/research support from: AbbVie, Astellas, Ayumi, Bristol-Myers Squibb, Chugai, Eisai, Eli Lilly, Kissei, Pfizer, Sanofi, Takeda, Tanabe-Mitsubishi, Speakers bureau: AbbVie, Astellas, Ayumi, Bristol-Myers Squibb, Chugai, Eli Lilly, Kissei, Pfizer, Sanofi, Tanabe-Mitsubishi, Actelion